Peran Muslim Sunni Moderat Dalam Menangkal Gerakan Ektrimisme Jama'at Nusrat Al-Islam Wal-Muslimin (JNIM) Di Pantai Gading - Riski Taufikur Rahman; Irfan Fauzi; Naufalun Ni’am (Research Institute and Community Engagement of UIN MADURA, 2026)
This study discusses the role of moderate Sunni Muslims in restraining the spread of extremism by Jama'at Nusrat al-Islam wal-Muslimin (JNIM) in Côte d'Ivoire. The research focuses on two main issues: the pattern of the jihadist Sahel network's expansion into northern Côte d'Ivoire, and the response of the Muslim community coordinated by Sunni Islamic organizations through proselytization, education, and strengthening social cohesion. This study employs a qualitative method based on literature review by examining scholarly articles and other related literature, and uses the Radicalization and Counter-Radicalization Theory to analyze radical influences and efforts to prevent them. The findings show that the threat to Côte d'Ivoire did not emerge abruptly, but developed as a spillover effect from conflicts in Mali and Burkina Faso, particularly through the northern border regions that are administratively weak and socioeconomically vulnerable. In this context, moderate Sunni Muslim communities, through religious organizations such as AMSCI, CODIS, and JEMCI, serve as ideological and social buffers by promoting a peaceful Islamic narrative, educating youth cadres, utilizing digital media, collaborating with the state, and involving Christian communities as a pluralistic nation. Nevertheless, the effectiveness of religious responses continues to depend on strengthening state presence, local economic development, and the governance of security in border areas.